Age alters gait compensations following meniscal injury in male rats. Issue 12 (14th March 2022) - Chan, Kiara M.; Yeater, Taylor D.; Allen, Kyle D.
Abstract: With age, susceptibility to osteoarthritis (OA) and OA‐related pain and disability increases. Like in OA patients, gait patterns in rodent OA models shift to protect the injured limb during loading. However, unlike in OA patients, it is unknown how age affects gait changes in rodent OA models. In this study, gait compensations following meniscal injury in 3‐, 6‐, and 9‐month‐old rats were evaluated to examine age‐effects of OA‐related joint dysfunction. Rats 3, 6, and 9 months received medial collateral ligament transection plus medial meniscus transection (MCLT + MMT) surgery ( n = 8/age group) or a skin incision ( n = 8/age group). Postsurgery, rats underwent gait testing at 2, 4, 6, and 8 weeks. Postmortem, joints were processed for histology to assess cartilage damage. MCLT + MMT rats walked with reduced vertical loading in their injured limbs immediately after injury and throughout OA progression. Compared to sham‐operated limbs, 6‐ and 9‐month MCLT + MMT animals reduced loading in their injured limbs while 3‐month MCLT + MMT animals did not. MCLT + MMT rats also increased stance time on the injured limb compared to the contralateral limb. Additionally, for the MCLT + MMT animals, 6‐ and 9‐month animals had significantly worse cartilage damage compared to 3‐month animals. These data indicated age at injury onset affects how animals load the OA‐affected joint, with older animals developing gait compensations that more markedly reduce weight on the injured limb during walking.